PENILAIAN TINGKAT KESEHATAN BANK DENGAN METODE RGEC PADA PT. BANK AGRIS TBK TAHUN 2013-2017 - Camelia Verahastuti, Mia Audina, Ivana Nina Esterlin Barus, (EKONOMIA, 2020)
The purpose of this study was to determine the assessment of the Bank's soundness with the RGEC method at PT. Bank Agris in 2013-2017 in terms of NPL, LDR, GCG, ROA, NIM and CAR.The analytical tool used is Non Performing Loan (NPL) , Loan to Deposit Ratio (LDR), Good Corporate Governance (GCG), Return On Assets (ROA). Net Interest Margin (NIM) dan Capital Adequacy Ratio (CAR).the data needed is 5 years from 2013 to 2017 obtained from the Indonesia Stock ExchangeThe results of this study : 1) NPL in 2013, 2014, 2015 the predicate obtained was very healthy while 2016 declined to be healthy and 2017 declined again to be quite healthy. 2) LDR in 2013 the predicate obtained was quite healthy while in 2014 it increased to become very healthy and then in 2015,2016 and 2017 it declined again to be healthy. 3) Good Corporate governance GCG in the Bank 2013-2017 predicate obtained by Bank Agris included in the healthy predicate. 4) ROA in 2013 had a fairly healthy predicate then in 2014,2015 and 2016 it fell to be unhealthy and 2017 decreased again to become unhealthy. 5) NIM in 2013 the predicate obtained was very healthy while in 2014 it declined to become a healthy predicate and increased again to become very healthy in 2015,2015 and 2016. 6) CAR in 2013-2017 predicate obtained was very healthy.The results of the hypothesis of this study Bank health rating with the RGEC method at PT. Bank Agris Tbk in 2013-2017 based on: 1) NPL in 2013, 2014, 2015 the predicate obtained from the NPL ratio was very healthy while 2016 declined to healthy and 2017 declining again to be quite healthy, the hypothesis is accepted. 2) LDR in 2013 the predicate obtained was quite healthy while in 2014 it increased to be very healthy and then in 2015,2016 and 2017 it declined again to be healthy, the hypothesis was accepted. 3) GCG in 2013-2017 the predicate obtained by Bank Agris is included in the predicate of health, the hypothesis is accepted. 4) 2013 ROA has a fairly healthy predicate then in 2014,2015 and 2016 it declined to be less healthy and 2017 declined again to become unhealthy, the hypothesis was rejected. 5) NIM In 2013 the predicate obtained was very healthy while in 2014 it declined to become a healthy predicate and increased to become very healthy in 2015,2015 and 2016, the hypothesis was accepted. 6) CAR In 2013-2017 the predicate obtained is very healthy, the hypothesis is accepted.